Synergistic effect of the inhibitors of RAF/MEK and AXL on KRAS‐mutated ovarian cancer cells with high AXL expression. Issue 6 (17th May 2020) - Umemura, Shiori; Sowa, Yoshihiro; Iizumi, Yosuke; Kitawaki, Jo; Sakai, Toshiyuki
Abstract: KRAS mutation is frequently seen in a subtype of ovarian cancer categorized as type 1. The KRAS‐MAPK pathway, which is closely involved in type 1 cancer progression, is under the regulation of receptor tyrosine kinases (RTKs). AXL, one of the RTKs, has been reported to be overexpressed in ovarian cancer and contributes to the poor prognosis. However, there is no useful target‐based agent against such gene profiles. We examined the combined effect of the dual RAF/MEK inhibitor CH5126766 and AXL inhibitor R428 on the growth of ovarian cancer HEY‐T30 and OVCAR‐5 cell lines, both of which bear KRAS mutation and express AXL at a high level, using the WST‐8 assay and the colony formation assay. The synergistic effect of the combination was evaluated by the combination index. The apoptotic cells were analyzed by flow cytometry. The expression of apoptotic proteins and the phosphorylation of MAPK and AKT pathway proteins were investigated by western blotting. We found that CH5126766 and R428 suppressed the phosphorylation of ERK and AKT, respectively, and their combination synergistically inhibited the growth of both cell lines with enhancement of apoptosis accompanied by the Bim upregulation. Combined treatment with CH5126766 and R428 is expected as the novel therapeutic option for KRAS ‐mutated ovarian cancer with high expression of AXL. Abstract : The combined treatment with a dual RAF/MEK inhibitor CH5126766 and AXL inhibitor R428 synergistically inhibited the growth of ovarian cancer HEY‐T30 and OVCAR‐5 cell lines, both of which bear KRAS mutation and express AXL at a high level, accompanied by inducing apoptosis.